Screening of Potato Cultivars to Potato Mop-Top Virus in Northwestern Pakistan - Muhammad Arif; Ghazala Ruby; Anayatur Rehman; Murad Ali; Shamsur Rehman (Potato Research, 2016)

Angiotensin Receptor Blockade Modulates NFκB and STAT3 Signaling and Inhibits Glial Activation and Neuroinflammation Better than Angiotensin-Converting Enzyme Inhibition - Shahnawaz Ali Bhat; Ruby Goel; Rakesh Shukla; Kashif Hanif (Molecular Neurobiology, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Uncertainty and feasibility of dynamical downscaling for modeling tropical cyclones for storm surge simulation - Zhaoqing Yang; Sourav Taraphdar; Taiping Wang; L. Ruby Leung; Molly Grear (Natural Hazards, 2016)

Mini-review: toxicity of mercury as a consequence of enzyme alteration - Ruby Ynalvez; Jose Gutierrez; Hector Gonzalez-Cantu (BioMetals, 2016)

Future hurricane storm surge risk for the U.S. gulf and Florida coasts based on projections of thermodynamic potential intensity - Karthik Balaguru; David R. Judi; L. Ruby Leung (Climatic Change, 2016)

Advances in Boerhaavia diffusa hairy root technology: a valuable pursuit for identifying strain sensitivity and up-scaling factors to refine metabolite yield and bioactivity potentials - Ruby Gupta; Pallavi Pandey; Sailendra Singh; Dhananjay Kumar Singh; Archana Saxena; Suaib Luqman; Dnyaneshwar U. Bawankule; Suchitra Banerjee (Protoplasma, 2016)

Circulating microRNA Signatures in Rodent Models of Pain - Rehman A. Qureshi; Yuzhen Tian; Marguerite K. McDonald; Kathryn E. Capasso; Sabrina R. Douglas; Ruby Gao; Irina A. Orlova; James E. Barrett; Seena K. Ajit; Ahmet Sacan (Molecular Neurobiology, 2016)

Observed variability of summer precipitation pattern and extreme events in East China associated with variations of the East Asian summer monsoon - Lei Wang; Yun Qian; Yaocun Zhang; Chun Zhao; L. Ruby Leung; Anning Huang; Chuliang Xiao (International Journal of Climatology, 2016)
This article presents a comprehensive analysis of interannual and interdecadal variations of summer precipitation and precipitation‐related extreme events in East China associated with variations of the East Asian summer monsoon ( EASM ) from 1979 to 2012. A high‐quality daily precipitation data set covering 2076 observational stations in China is analysed. Based on the precipitation pattern analysis using empirical orthogonal functions and the regime shift detection method, three sub‐periods of 1979–1992 (period I), 1993–1999 (period II ) and 2000–2012 (period III ) are identified to be representative of the precipitation variability. Similar significant variability of the extreme precipitation indices is found across four sub‐regions in eastern China. The spatial patterns of summer mean precipitation, the number of days with daily rainfall exceeding 95th percentile precipitation (R95p) and the maximum number of consecutive wet days ( CWD ) anomalies are consistent, but opposite to that of maximum consecutive dry days ( CDD ) anomalies to some extent during the three sub‐periods. However, the spatial patterns of hydroclimatic intensity ( HY‐INT ) are notably different from that of the other three extreme indices, but highly correlated to the dry events. The changes of precipitation anomaly patterns are accompanied by the change of the EASM regime and the abrupt shift of the position of the west Pacific subtropical high around 1992/1993 and 1999/2000, respectively, which influence the moisture transport and contributes to the precipitation anomalies. In addition, the EASM intensity is linked to sea surface temperature anomaly over the tropical Indian and Pacific Ocean through its effects on convective activity over the west Pacific that induces the cyclonic or anticyclonic anomaly over the South China and northwest Pacific.

Polycystic ovarian syndrome (PCOS), related symptoms/sequelae, and breast cancer risk in a population-based case–control study - Jayeon Kim; Jennifer E. Mersereau; Nikhil Khankari; Patrick T. Bradshaw; Lauren E. McCullough; Rebecca Cleveland; Sumitra Shantakumar; Susan L. Teitelbuam; Alfred I. Neugut; Ruby T. Senie; Marilie D. Gammon (Cancer Causes & Control, 2016)

North American extreme temperature events and related large scale meteorological patterns: a review of statistical methods, dynamics, modeling, and trends - Richard Grotjahn; Robert Black; Ruby Leung; Michael F. Wehner; Mathew Barlow; Mike Bosilovich; Alexander Gershunov; William J. Gutowski; John R. Gyakum; Richard W. Katz; Yun-Young Lee; Young-Kwon Lim; et al. (Climate Dynamics, 2016)

Attributing runoff changes to climate variability and human activities: uncertainty analysis using four monthly water balance models - Shuai Li; Lihua Xiong; Hong-Yi Li; L. Ruby Leung; Yonas Demissie (Stochastic Environmental Research and Risk Assessment, 2016)

Parapheromones for Thynnine Wasps - Björn Bohman; Amir Karton; Ruby C. M. Dixon; Russell A. Barrow; Rod Peakall (Journal of Chemical Ecology, 2016)